Nowcasting Regional GDP: The Case of the Free State of Saxony - Steffen Henzel; Robert Lehmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2015)
We tackle the nowcasting problem at the regional level using a large set of indicators (regional, national and international) for the years 1998 to 2013. We explicitly use the ragged-edge data structure and consider the different information sets faced by a regional forecaster within each quarter. It appears that regional survey results in particular improve forecasting accuracy. Among the 10% best performing models for the short forecasting horizon, one fourth contain regional indicators. Hard indicators from the German manufacturing sector and the Composite Leading Indicator for Europe also deliver useful information for the prediction of regional GDP in Saxony. Unlike national GDP forecasts, the performance of regional GDP is similar across different information sets within a quarter.
Keywords: C22; C52; C53; E37; R11; 330; nowcasting; regional gross domestic product; bridge equations; regional economic forecasting; mixed frequency